2006
DOI: 10.1074/jbc.m507695200
|View full text |Cite
|
Sign up to set email alerts
|

Reuptake of Extracellular Amelogenin by Dental Epithelial Cells Results in Increased Levels of Amelogenin mRNA through Enhanced mRNA Stabilization

Abstract: Amelogenin is an extracellular matrix protein secreted by ameloblasts and is a major component of enamel matrix. Recently, in addition to their role in enamel formation, the biological activity of enamel proteins in the process of cell differentiation has recently become widely appreciated. In this study, we examined the biological activity of amelogenin on ameloblast differentiation. Recombinant mouse amelogenin (rm-amelogenin) enhanced the expression of endogenous amelogenin mRNA in a cultured dental epithel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 36 publications
(43 reference statements)
4
31
1
Order By: Relevance
“…Amelogenin or its fragments are endocytosed by ameloblasts via a receptor-mediated mechanism involving LAMP1 and CD63 proteins (Shapiro et al, 2007). This uptake may serve as a feedback loop to upregulate amelogenin expression through stabilization of its mRNA in the cytoplasm (Xu et al, 2006). We did not find evidence for the direct involvement of avb6 integrin in amelogenin endocytosis.…”
Section: Discussioncontrasting
confidence: 42%
“…Amelogenin or its fragments are endocytosed by ameloblasts via a receptor-mediated mechanism involving LAMP1 and CD63 proteins (Shapiro et al, 2007). This uptake may serve as a feedback loop to upregulate amelogenin expression through stabilization of its mRNA in the cytoplasm (Xu et al, 2006). We did not find evidence for the direct involvement of avb6 integrin in amelogenin endocytosis.…”
Section: Discussioncontrasting
confidence: 42%
“…The specific amelogenin gene splice products induce expression of the bone matrix proteins bone sialoprotein (BSP) and BAG-75 in culture and in an implant in vivo [5]. We previously demonstrated that the reuptake of full-length amelogenin protein results in increased levels of amelogenin mRNA through enhanced mRNA stabilization [6,7]. These findings indicated that amelogenin proteins are important for both ameloblast and odentoblast differentiation in an autocrine or paracrine manner.…”
Section: Introductionmentioning
confidence: 98%
“…The mRNA levels of differentiation-related marker genes were determined by quantitative real-time PCR as described previously [6,7,[16][17][18][19]. Briefly, total RNA was extracted at various points with ISOGEN (Nippon Gene, Japan).…”
Section: Rna Extraction and Real-time Pcr Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the Mmp20 null mouse and human kindreds with critical MMP20 mutations have brittle enamel that tends to delaminate from the dentin surface (Caterina et al, 2002;Kim et al, 2005;Ozdemir et al, 2005). It is believed that ameloblasts respond to changes in the extracellular matrix by adjusting their activities to maintain conditions appropriate for biomineralization (Xu et al, 2006).…”
Section: Introductionmentioning
confidence: 99%